Liberia : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
Liberia remains at moderate risk of debt distress, though care and precision in implementing its ambitious infrastructure program will be critical. Under the baseline scenario, which reflects staff’s interpretation of the authorities’ stated plans, Liberia will remain at moderate risk of debt distress but move closer to thresholds that mark a high probability of debt distress. Adverse risks to the baseline are also significant. Staff discussed an alternative reform scenario that would ease the risk of debt distress while achieving roughly the same level of spending. The reform scenario assumes that all external financing would be on concessional terms and the amount of additional borrowing would be strictly controlled and supplemented with domestic resource mobilization. Such steps would be beneficial not only to improve the safety margin for the preservation of debt and macroeconomic stability, but also to sustain broad-based growth over the forecast horizon.